Wealth-Income Ratios in Free Market Capitalism: Switzerland, 1900-2020 - Enea Baselgia; Isabel Z. Martínez (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate the ratio of private wealth to national income, βpt, for Switzerland from 1900 to 2020. Our results indicate that over the 20th century, βpt did not follow a U-shaped pattern as in most European countries. Instead, its was exceptionally stable at around 500%. We argue that this consistently high βpt was the result of geopolitical factors combined with Switzerland's capital friendly policy-making. Since the turn of the century, however, βpt has been on a rapid rise to reach 793% in 2020. This considerable increase is mainly driven by large capital gains, especially in housing wealth.
Keywords: N34; D31; D33; E01; 330; wealth-income ratio; distribution; economic growth; housing prices